Nilai Kepemimpinan Edukatif Ki Hajar Dewantara Dalam Perspektif Tafsir Ibn Kathir atas Surat Ali Imran:159 - Ratna Sundari Puspitosari; Enjang Burhanudin Yusuf (Indonesian Journal Publisher, 2025)
Ki Hajar Dewantara, as the Father of Indonesian Education, inherited the philosophy of educational leadership known as